2011
DOI: 10.1127/1863-9135/2011/0178-0111
|View full text |Cite
|
Sign up to set email alerts
|

Drift distance of macroinvertebrates throughout summer in headwater tributaries of the Calapooia River

Abstract: Drifting invertebrates from small headwater streams are a food subsidy for fi shes and other downstream consumers in larger streams. This subsidy can become especially important for stream fi shes during summer due to high metabolic demand caused by elevated water temperatures. The source length in small streams contributing these drifting invertebrates to fi sh bearing habitat has not been established. We conducted an experiment to determine if summer drift delivered by headwater streams to larger channels is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In daytime‐only sampling, Urabe et al () found highly variable results with a range of 0.008–0.062 mg m −3 in mountainous Japanese streams. In even smaller streams, Wipfli and Gregovich () in south‐east Alaska, and Danehy et al () in Calapooia River tributaries, found drift concentration biomass in headwater streams in late summer of 1–4 mg m −3 and 0.2–1.1 mg m −3 , respectively. Overall observed drift concentrations are within the range of variability seen elsewhere.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In daytime‐only sampling, Urabe et al () found highly variable results with a range of 0.008–0.062 mg m −3 in mountainous Japanese streams. In even smaller streams, Wipfli and Gregovich () in south‐east Alaska, and Danehy et al () in Calapooia River tributaries, found drift concentration biomass in headwater streams in late summer of 1–4 mg m −3 and 0.2–1.1 mg m −3 , respectively. Overall observed drift concentrations are within the range of variability seen elsewhere.…”
Section: Discussionmentioning
confidence: 95%
“…Summer baseflow is a physical and energetic bottleneck for reasons beyond the obvious constraint of elevated stream temperatures. Drift distance of individual invertebrates is shorter at baseflow than higher flow (Danehy, Langshaw, Duke, & Bilby, ; Elliott, ; McLay, ; Sagar & Glova, ), potentially lowering drift concentration. Lower flows reduce suitable feeding locations for individual fish (Fausch, ; Hayes, Hughes, & Kelly, ), which affects population growth (Mellina & Hinch, ; Rosenfeld, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, drifting invertebrates travel shorter distances during periods of low discharge, which can further reduce prey availability at foraging locations (Danehy et al. ). Significant decreases in rates of prey delivery depress growth rates of closely related Rainbow Trout O. mykiss under the direct manipulation of discharges (Harvey et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, taxonomic composition of the macroinvertebrate benthos at stream inflows was not measurably changed by the drift of stream taxa. Drift distances can be short (Danehy et al. , 2011) and proportional to stream size (Kiffney et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, taxonomic composition of the macroinvertebrate benthos at stream inflows was not measurably changed by the drift of stream taxa. Drift distances can be short (Danehy et al, 2011) and proportional to stream size (Kiffney et al, 2006); thus, the minimal impact observed on littoral macroinvertebrate biomass and composition might be due to the small size of the streams. Alternatively, if stream taxa were consumed selectively by C. asper, the composition of the macroinvertebrate benthos might be similar in both inflow and control plots.…”
Section: Discussionmentioning
confidence: 99%